Advances on whole genome sequencing in Triticeae - KUANG Liuhui; LI Qi; ZHANG Guoping (浙江大学学报. 农业与生命科学版)
The Triticeae provides the important cereal crops, such as wheat, barley, and rye, which produces approximately 9×108 t annually, accounting for about 30% of the total global cereal production. However, Triticeae genomes are relatively difficult to be de novo sequenced and assembled due to their large genome size, a high proportion of repeat sequences, and different ploidy levels. With the rapid development of third-generation long read sequencing technologies and assembly algorithms designed for complex genomes, and also the falling cost of genome sequencing in recent years, more and more Triticeae species have been successfully sequenced. In this study, we reviewed the advances on the whole genome sequencing of 17 Triticeae species (including subspecies), including Triticum, Hordeum, Secale, Elytrigia, and Aegilops, in aspects of sequencing technology, assembly strategy and quality, and the major research contents associated with genomes and gene functions. This review may provide the references for sequencing strategies and genomic studies of other more complex plant genomes.